Physicochemical properties of catechin/β-cyclodextrin inclusion complex obtained via co-precipitation. Issue 1 (1st January 2019) - Jiang, Longwei; Yang, Jingde; Wang, Qian; Ren, Lili; Zhou, Jiang
ABSTRACT: Inclusion complex of catechin (CAT) with β-cyclodextrin (β-CD) was prepared using co-precipitation method to enhance antioxidant stability of CAT and the physicochemical properties of the inclusion complex were studied. The CAT/β-CD inclusion complex was analyzed through phase solubility study, Fourier transform infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC), scanning electron microscopy (SEM) and X-ray diffraction (XRD). Phase solubility study indicated that CAT and β-CD formed 1:1 stoichiometric inclusion complex. Results of FT-IR indicated that CAT was stabilized in β-CD cavity by intra-molecular hydrogen bonds. Results of DSC and SEM proved that CAT/β-CD inclusion complex formed. XRD results showed that the formation of new solid crystalline phases in the CAT/β-CD inclusion complex. CAT was effectively protected through encapsulation into β-CD and the antioxidant stability of CAT was improved after encapsulation. In addition, the release behavior of CAT from the inclusion complex increased with increasing of the temperature.